Kefir, source of hydrolase enzymes and bacteria with potential to degrade pet-type plastics - Rubio-Piña, Jorge; Tenorio-Salgado, Silvia; Peniche-Cartas, Samantha; Ferraez-Balam, Johan; Mis-Ruz, Kristal; Zetina-Irizzont, Joaquín; Moo-Huchim, Victor Manuel; Rivera-Muñoz, Gerardo; Solis-Pereira, Sara; Lizama-Uc, Gabriel (Ecosistemas y Recursos Agropecuarios, 2022)
Kefir is a fermented milk product that contains a symbiotic microbiota that generates health benefits by synthesizing different metabolites and enzymes with diverse metabolic capacities. For their part, synthetic plastics used in the home and industrial sectors have caused an environmental problem around the world due to excessive use, their high durability and lack of recycling. For this reason, Kefir consortia are studied as a source of hydrolytic enzymes and microorganisms capable of degrading plastics. For this, two kefir metagenomes (NCBI under the BioProject PRJNA704713) were analyzed, using bioinformatic tools, aimed at the search for sequences homologous to hydrolases, as well as the isolation of microorganisms that degrade PET-type plastics. The results obtained allowed the identification of two kefir sequences homologous to the dienelactone hydrolase enzyme (DLH-1 and DHL-2), which can participate in the degradation of plastic compounds. Both sequences presented a shared domain with the alpha/beta hydrolase superfamily; this type of motif has been observed in PET hydrolases obtained from different species of actinomycetes. Likewise, microorganisms with the capacity to degrade PLC plastics were isolated, suggesting that they possess enzymes with hydrolytic activity of industrial compounds for the manufacture of PET. In conclusion, our data demonstrate that kefirs are sources of hydrolytic enzymes of PET hydrolases and that it is possible to isolate PET-degrading microorganisms from them.